A case study on the interplay between thyroid storm and hepatic impairment - Kibria, Kazi Golum; Aktar, Yasmin; Alam, Shahinul (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
A 40-year-old lady presented with complaints of fever, jaundice, anorexia, weight loss, nausea, and vomiting. She had experienced palpitations, heat intolerance, and about 10kg weight loss within a year. But she ignored and did not seek any medical advice. Her presenting vitals were: heart rate: 124 beats per minute, regular; respiratory rate: 24 breaths per minute; blood pressure: 90/60 mmHg; and temperature: 1010F. The woman looked emaciated with the prominence of her zygomatic bones, had a mild diffuse goiter, and was severely icteric. However, there was no evidence of proptosis. Laboratory workup on admission showed significantly raised bilirubin and aspartate aminotransferase, along with biochemical evidence of hyperthyroidism. The diagnosis of Graves’ Disease was further approved by a high level of thyroid receptor antibody and diffuse enlargement of the thyroid on ultrasound. Hepatitis was also evident on ultrasound, with reduced parenchymal echogenicity and increased periportal echoes. According to the Burch-Wartofsky Point Scale, the score was 45 to categorize her as a case of thyroid storm. All relevant etiologies of hepatitis (Anti-HEV IgM, Anti-HAV IgM, Anti-HCV, HBsAg, including Anti-Nuclear Antibody (ANA), Anti-Smooth Muscle Ab, and Anti-Mitochondrial IgG) were excluded. Initially, the patient was resuscitated with fluids, and symptomatic treatment was provided. Later, she was managed with intravenous corticosteroid, carbimazole, and ß-blocker. She was discharged after two weeks with significant improvement in her clinical and biochemical profiles. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S57]